Sputum induction for the diagnosis of tuberculosis. Issue 6 (June 1996) - Shata, A M; Coulter, J B; Parry, C M; Ching'ani, G; Broadhead, R L; Hart, C A
Abstract : Confirmation of tuberculosis in young children is difficult as they seldom expectorate sputum. Gastric aspirates are invasive and stressful and like laryngeal swabs are seldom smear positive. Induction of sputum by nebulised hypertonic saline (3%) was attempted in 30 Malawian children aged 3-15 years and was successful in 29. Four sputa were smear positive and Mycobacterium tuberculosis was cultured from three of them. A further four sputa were culture positive though smear negative. In all, the diagnosis of tuberculosis was confirmed in eight (28%) of 29 children. The presence of polymorphonuclear cells in the specimen was indicative of sputum, in contrast to epithelial cells which originate from saliva. A predominance of polymorphonuclear cells in specimens was more common in older children and these specimens were more likely to be smear positive or culture positive. Sputum induction is a useful method for the confirmation of tuberculosis and is possible in young children.